Serum Zinc Concentration Correlates With Ferritin Concentration in Patients Undergoing Peritoneal Dialysis: A Cross-Sectional Study - Kaneko, Shohei; Morino, Junki; Minato, Saori; Yanai, Katsunori; Mutsuyoshi, Yuko; Ishii, Hiroki; Matsuyama, Momoko; Kitano, Taisuke; Shindo, Mitsutoshi; Aomatsu, Akinori; Miyazawa, Haruhisa; Ueda, Yuichiro; et al. (Frontiers in Medicine, 2020)
Background: The prevalence and clinical effects of zinc deficiency in patients undergoing peritoneal dialysis (PD) have not been fully established. Methods: This was a retrospective, cross-sectional study. The prevalence of serum zinc deficiency and the clinical factors related to serum zinc concentration were determined in 49 patients undergoing PD (mean age 59.5 years (± 14.8 years), 38/49 were men (78.6%), median PD period 24.0 months (12.5–45.0 months)). A serum zinc concentration < 60 μg/dL was defined as serum zinc deficiency, and a serum zinc concentration between 60 and 80 μg/dL as possible serum zinc deficiency. Results: Serum zinc deficiency was present in 51% (25/49) of the patients, and possible serum zinc deficiency was present in 45% (22/49) of patients undergoing PD. Multivariate analysis showed that serum zinc concentration significantly correlated with serum ferritin concentration (β = 0.357, P < 0.01). Conclusions: The prevalences of serum zinc deficiency and possible serum deficiency are high and serum zinc concentration correlates with serum ferritin concentration in patients undergoing PD.